2015
DOI: 10.1155/2015/878235
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Esthetic Properties of Developmental Defects of Enamel: A Spectrophotometric Clinical Study

Abstract: Objectives. Detailed clinical quantification of optical properties of developmental defect of enamel is possible with spectrophotometric evaluation. Developmental defects of enamel (DDE) are daily encountered in clinical practice. DDE are an alteration in quality and quantity of the enamel, caused by disruption and/or damage to the enamel organ during amelogenesis. Methods. Several clinical indices have been developed to categorize enamel defects based on their nature, appearance, microscopic features, or caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…Opacities located on the more translucent incisal third of the tooth are more noticeable, by virtue of their opaque nature. 14 If the patient has a short upper lip length, incompetent oral seal and/or proclined incisors, the opacity may also be subject to drying and may be even more visible. In this study, all opacities were located in the incisal third of affected incisors, although the details about the patient's lip line were not recorded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Opacities located on the more translucent incisal third of the tooth are more noticeable, by virtue of their opaque nature. 14 If the patient has a short upper lip length, incompetent oral seal and/or proclined incisors, the opacity may also be subject to drying and may be even more visible. In this study, all opacities were located in the incisal third of affected incisors, although the details about the patient's lip line were not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, attempts to measure tooth colour by the human eye are highly susceptible to bias. 14 Investigators have therefore sought to employ image analysis techniques to provide more objective and reproducible measurements of enamel colour/characteristics. Notably, Kim and co-workers 9 appear to have been the first to use image analysis software to evaluate the effectiveness of treatment in improving the aesthetics of both anterior enamel opacities and post-orthodontic decalcification lesions in young patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with what claimed by Artun (29) who observed that the retainer could have a positive effect on oral hygiene: "The presence of an orthodontic wire applied with a retentive aim, at short and long term, with plaque and calculus build-up, does not appear to prevent hygiene which results to be adequate even along the gingival margin. In this regard, the motivation, possibly transmitted by the orthodontist while giving the contention device, results to be the main success factor" (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Several clinical indices have been developed to categorize enamel defects and they can be divided into (a) Specific fluorosis indices which identify and categorize only dental fluorosis, and (b) Descriptive indices with no etiological assumption .The modified DDE Index is a descriptive index. It is more practical and comparable index for epidemiological studies and it allows efficient recording of prevalence and severity of enamel defects (9). .…”
Section: Developmental Enamel Defects (Dde) Have Beenmentioning
confidence: 99%